Implementing web applications in the English as a foreign language classroom to develop learners’ productive skills: The case of Kazakhstan - Shelestova, T.; Nabiyeva, A.; Kalizhanova, A. (The JALT CALL Journal, 2023)
The paper reports the results of an exploratory quantitative study investigating the potential of VoiceThread and Flipgrid as learning tools for the development of learners’ productive skills and enhancing learners’ performance to provide the basis for continuing independent practice. The study involved a total of 39 students in a four-week English course; 19 students used the VoiceThread and Flipgrid software, and 20 students in a control group followed the same curriculum but without these web applications. Students carried out a weekly extended speaking task (storytelling) on a topic related to the curriculum. To prepare for this, they used VoiceThread and Flipgrid software to record and rehearse their presentation for other students and for the teacher to listen to and provide individual feedback. The recordings were analyzed according to the Speaking Assessment Scale. Questionnaires were used to investigate learners’ perceptions of the task’s value and of their performance and confidence changes over time. The results showed that regular VoiceThread and Flipgrid tasks help learners develop their productive skills, performance, and confidence in spoken English. Such voice-recording activities have the potential to improve speaking and writing and thus tackle the limitations on time, practice, and feedback inherent in classroom-based courses.
Keywords: web applications; web 2.0 tools; VoiceThread; Flipgrid; productive skills; scaffolding; technology-based teaching; English as a foreign language